A novel thermodynamic and heat and mass transfer model for the multicylinder dryer section of a paper machine. Issue 7 (10th June 2022) - Anjomshoaa, Ali; Salmanzadeh, Mazyar
Abstract: Modeling of the dryer section of a paper machine is of high importance in both designing and operation points of view. In this research, a novel thermodynamic and heat and mass transfer model has been introduced. The model is based on empirical equations of the literature and does not need fine discretization techniques such as finite difference method. The method used for calculation of convective heat and mass transfer coefficients of the dryer is a modification of the methods utilized in the literature. The trend of paper and air temperature in the dryer, the steam consumption of each cylinder, as well as the trend of drying process throughout the dryer has been calculated. Overall results of the dryer such as the total evaporated water and the specific steam consumption of the dryer have been obtained too. The results have been validated with experimental data of a previous research in the literature and show a relatively good agreement with the experimental data. Finally, the sensitivity of the results to some main parameters has been analyzed.